How Psychotherapists Experience Burnout/An Interpretative Phenomenological Analysis - Drakouli Stratoniki (2014)
Introduction, Literature Review, Origin and Definition of Burnout, Antecedents of Burnout, Preventive-Coping Strategies, Burnout and Psychotherapists, Methodology, Research Question, Sample, Data Collection, Data Analysis, Ethical Considerations, Results, Discussion, Conclusion, References, Appendices.